-2(4x+9)=-8x-18

Simple and best practice solution for -2(4x+9)=-8x-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4x+9)=-8x-18 equation:


Simplifying
-2(4x + 9) = -8x + -18

Reorder the terms:
-2(9 + 4x) = -8x + -18
(9 * -2 + 4x * -2) = -8x + -18
(-18 + -8x) = -8x + -18

Reorder the terms:
-18 + -8x = -18 + -8x

Add '18' to each side of the equation.
-18 + 18 + -8x = -18 + 18 + -8x

Combine like terms: -18 + 18 = 0
0 + -8x = -18 + 18 + -8x
-8x = -18 + 18 + -8x

Combine like terms: -18 + 18 = 0
-8x = 0 + -8x
-8x = -8x

Add '8x' to each side of the equation.
-8x + 8x = -8x + 8x

Combine like terms: -8x + 8x = 0
0 = -8x + 8x

Combine like terms: -8x + 8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 8.77xy=8.00 | | x+7x-8=8 | | (3x-9)(x+4)=0 | | 4y+228=52 | | 12a-24=12 | | 3x+4(x+3)=68 | | 3x-8+x+12=17 | | -15*5/3c*8 | | -5(2x-1)=3(x+5) | | 56y+1=781 | | 6x+8=290 | | -3+1=x+9-4x | | v/4-10=5 | | 1.5x-18=0.5x | | 22/11x9-3 | | -4/3+x2+1/3x-8+8/3x | | 5v^2=20 | | 2/63/6= | | (2r-4s+6t)(2r-4s+6t)= | | 5y+y-9=8y+1 | | 4+12/4-2 | | 80x^2=50 | | 3(a-5)=6a(3a+15) | | -4/3+t2+1/3t-8+8/3t | | (a/6)-11=25 | | (3xy^2)(-5x^3y)= | | 4x-25x^1/2+25=0 | | 8x-36=8 | | ax-bx=-cforx | | -20c+3-3c+13= | | x-.20=64 | | 6.8x-4.7=17.62 |

Equations solver categories